Light source estimation using feature points from specular highlights and cast shadows - Bunteong Anusorn; Chotikakamthorn Nopporn (My University, 2016)
A method for light sources estimation is proposed in this paper. The method utilizes feature points in cast shadows to estimate near light source positions from estimated source directions using specular highlights. There are several methods that can be used to estimate light sources from scene images, using either cast shadows or specular highlights. However, most of them are limited to directional light sources. The proposed method can estimate the positions and intensities of multiple near point light sources. Specular highlights on an object of known geometry are first used for light source direction estimation. Then, a discontinuity point in the object shape and the corresponding cast shadow on a ground plane are used for light source position estimation. Feature points obtained from an image of the cast shadow, however, can be inaccurate due to various factors. Information on diffused light reflected from Lambertian ground-plane surface is subsequently used to improve estimation accuracy. Experimental results were used to evaluate the performance of the proposed method. Key words: Light source estimation, light source recovery, augmented reality.
Keywords: Specular highlight; Feature (linguistics); Point source; Position (finance); Discontinuity (linguistics); Advanced Vision and Imaging